2024
DOI: 10.1101/2024.03.08.583971
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transcranial Functional Ultrasound Imaging Detects Focused Ultrasound Neuromodulation Induced Hemodynamic Changes in Mouse and Nonhuman Primate BrainsIn Vivo

Christian Aurup,
Jonas Bendig,
Samuel G. Blackman
et al.

Abstract: Focused ultrasound (FUS) is an emerging noinvasive technique for neuromodulation in the central nervous system (CNS). To evaluate the effects of FUS-induced neuromodulation, many studies used behavioral changes, functional magnetic resonance imaging (fMRI) or electroencephalography (EEG). However, behavioral readouts are often not easily mapped to specific brain activity, EEG has low spatial resolution limited to the surface of the brain and fMRI requires a large importable scanner that limits additional reado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 73 publications
0
1
0
Order By: Relevance
“…We recently reported hemodynamic responses evoked by FUS in mice and nonhuman primates via transcranial fUS [41]. The study reported bilateral responses with center sonication and less localized hemodynamic responses with left or right sonication, which may be largely due to a large focal size of 1.68 MHz FUS transducer without in situ displacement targeting, and the presence of the skull.…”
Section: Discussionmentioning
confidence: 99%
“…We recently reported hemodynamic responses evoked by FUS in mice and nonhuman primates via transcranial fUS [41]. The study reported bilateral responses with center sonication and less localized hemodynamic responses with left or right sonication, which may be largely due to a large focal size of 1.68 MHz FUS transducer without in situ displacement targeting, and the presence of the skull.…”
Section: Discussionmentioning
confidence: 99%